The sementics of Ugaritic Comparative research according to Arabic - الراهب سميرة (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
This research is based on comparisons between Arabic and Ugaritic. The considered side requires both theoretical and practical requirements . The theoretical requirement is for prepare an Arabic lexicon demonstrates the Lingual developments and describe the Ugaritic language semanticlly. The practical one is by etymoning . it means studying the etymons of the Arabic vocabularies in the ancient semantic . and prepare for Ugaritic lexicon The Ugaritic language is considered as a practical example of the semitic language in the comparative analysis for the lexical and semantic phenomena Arabic is one of the nearest languages to the Ugaritic, and both of them retain the ancient sematic language structure .